Thomas' Calculus 13th Edition

Published by Pearson
ISBN 10: 0-32187-896-5
ISBN 13: 978-0-32187-896-0

Chapter 14: Partial Derivatives - Section 14.3 - Partial Derivatives - Exercises 14.3 - Page 808: 59


$\dfrac{1}{2}$ and $\dfrac{3}{4}$

Work Step by Step

We know that $f_x(x_0,y_0)=\lim\limits_{h \to 0} \dfrac{f(x_0+h,y_0)-f(x_0,y_0)}{h}$ $f_x(-2,3)=\lim\limits_{h \to 0} \dfrac{f(-2+h,3)-f(-2,3)}{h}=\lim\limits_{h \to 0} \dfrac{\sqrt {2h+4}-2}{h}=\lim\limits_{h \to 0} \dfrac{2}{\sqrt {2h+4}-2}=\dfrac{1}{2}$ Also, $f_y(x_0,y_0)=\lim\limits_{h \to 0} \dfrac{f(x_0,y_0+h)-f(x_0,y_0)}{h}$ Now,$f_y(-2,3)=\lim\limits_{h \to 0} \dfrac{f(-2,3+h)-f(-2,3)}{h}=\lim\limits_{h \to 0} \dfrac{\sqrt {3h+4}-2}{h}=\lim\limits_{h \to 0} \dfrac{3}{\sqrt {3h+4}-2}=\dfrac{3}{4}$
Update this answer!

You can help us out by revising, improving and updating this answer.

Update this answer

After you claim an answer you’ll have 24 hours to send in a draft. An editor will review the submission and either publish your submission or provide feedback.